2010
DOI: 10.1007/s11517-010-0639-5
|View full text |Cite
|
Sign up to set email alerts
|

Static magnetic field exposure promotes differentiation of osteoblastic cells grown on the surface of a poly-l-lactide substrate

Abstract: This study investigated the effects of static magnetic fields on the differentiation of MG63 cells cultured on the surface of poly-L-lactide (PLLA) substrates. The cells were continuously exposed to a 4,000 Gauss-static magnetic field (SMF) for 5 days. The proliferation effects of the SMF were measured by MTT assay. Morphologic changes and extracellular matrix release were observed by scanning electron microscopy. The effects of the SMF on alkaline phosphatase activity levels were compared between exposed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 31 publications
2
29
0
3
Order By: Relevance
“…Huang et al [49] reported an increased expression of Col-I in osteoblasts cultured under 0.4 T SMF whilst Feng et al have shown increased ALP activity in cells cultured under a 0.4 T SMF. Although the effect of SMF exposition increases expression of genes responsible for osteogenesis (and this has been proven on osteoblasts cells) its effect on stem cells has not yet been fully determined [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al [49] reported an increased expression of Col-I in osteoblasts cultured under 0.4 T SMF whilst Feng et al have shown increased ALP activity in cells cultured under a 0.4 T SMF. Although the effect of SMF exposition increases expression of genes responsible for osteogenesis (and this has been proven on osteoblasts cells) its effect on stem cells has not yet been fully determined [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, magnetism has been found to positively impact cellular responses [911]. Plenty of magnetic composite materials that integrate with magnetic nanoparticles (MNPs) have been manufactured to accelerate the repair and regeneration of engineering tissues [10,1217].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, calcium phosphate cements macerated with ultrafine MNPs have significant promotional effects on cell adhesion, proliferation and differentiation [15]. Additionally, biopolymer nanocomposite scaffolds mixed with MNPs increased the adhesion and differentiation of osteoblastic cells in vitro and bone formation in vivo [9,12,14]. From the above examples, MNPs can be considered a valid stimulus to bone fracture healing and new bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…Moderate-intensity SMFs (1 mT-1 T) have been identified capable of affecting a number of biological behaviors of osteoblastic cells [16,17], and it is particularly interesting to researchers because it is easily achieved with permanent magnets. However, the effect of SMF on osteogenic differentiation of osteoblastic cells on magnetic nanofibrous scaffolds of different magnetic properties remains unclear.…”
Section: Introductionmentioning
confidence: 99%